Preparation method and application of high-stability NiS / NiMoO4 electro-catalytic material

Through the modification of NiMoO4 by hydrothermal method and vulcanization process, high-stability NiS/NiMoO4 electrocatalytic materials were prepared, which solved the problems of high cost and poor stability of existing precious metal catalysts, achieved efficient catalytic performance and long-term stability under alkaline conditions, and had good industrial application prospects.

CN119877017AInactive Publication Date: 2025-04-25NANTONG UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510059436.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-04-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the prior art, high costs and scarcity limit the application of precious metals Pt and Ir/Ru-based materials in large-scale hydrogen energy preparation, and there is still room for improvement in stability and efficiency of existing bimetal oxide catalysts.

Method used

NiMoO4 material was modified by hydrothermal method and vulcanization process to prepare a high-stability NiS/NiMoO4 electrocatalytic material. This material has a nanorod array structure and can exhibit excellent catalytic activity and long-term durability under alkaline conditions.

Benefits of technology

It achieves the catalytic performance of HER and OER with low overpotential and high current density under alkaline conditions, and the long-term stability and total water-removing performance of the material are excellent, making it suitable for industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119877017A_ABST
    Figure CN119877017A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of electrocatalytic materials, in particular to a preparation method and application of a high-stability NiS / NiMoO4 electrocatalytic material.The preparation method comprises the steps that 1, 0.01 M (NH4) 6Mo7O24. 4H2O and Ni (NO3) 2.6 H2O are dissolved with 75 mL of distilled water respectively, and the whole solution system is magnetically stirred for 30 min to form a uniform solution; then, transferring the uniform solution into a 50mL high-pressure kettle with a polytetrafluoroethylene lining, and immersing the treated foamed nickel into the high-pressure kettle; sealing the autoclave at 150 DEG C for 6 hours, washing the autoclave with deionized water and ethanol for several times until the autoclave is neutral, and performing vacuum drying to obtain NiMoO4 / NF; and 2, placing powdered sulfur on the upstream of the foamed nickel, placing the powdered sulfur in a tubular furnace, carrying out vulcanization in a nitrogen atmosphere, washing the foamed nickel, and drying the foamed nickel in a vacuum oven overnight to obtain the NiS / NiMoO4 electro-catalytic material. The high-stability NiS / NiMoO4 electro-catalytic material is prepared by utilizing a hydrothermal method and a tubular furnace vulcanization method, has excellent HER, OER and stability, and has a good application prospect in industry.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrocatalytic materials, and in particular to a preparation method and application of a high-stability NiS / NiMoO4 electrocatalytic material. Background Art

[0002] Given that hydrogen energy has the advantages of high energy density, diverse utilization methods and zero carbon emissions, it is unique among various new energy sources and can be regarded as an ideal choice to replace fossil fuels. The electrocatalytic decomposition of water, including hydrogen evolution reaction (HER) and oxygen evolution reaction (OER), is regarded as the optimal strategy for hydrogen production due to its environmentally friendly characteristics and abundant water resources. However, due to the low energy consumption of the uphill reaction and the need for a high overpotential, the cost is high. In order to improve energy efficiency and enhance the feasibility of such methods, highly active electrocatalysts play a vital role in large-scale hydrogen production. Although Pt and Ir / Ru-based materials are good HER and OER electrocatalysts, their high prices and scarcity on the earth make it difficult to achieve large-scale application. Therefore, finding a low-cost, high-efficiency non-precious metal bifunctional electrocatalyst will be an ideal choice to accelerate the development of hydrogen energy.

[0003] Compared with single-component oxide materials, bimetallic oxides have become a research hotspot due to their excellent catalytic performance. In particular, transition metal molybdates have won wide attention from researchers due to their excellent electrical conductivity and high electrochemical specific surface area contributed by the polymorphism of molybdenum. Among these materials, bimetallic NiMoO4 is regarded as a potential material with broad application prospects, which is mainly due to the synergistic effect between the excellent redox properties of Ni and the high conductivity of Mo, which gives NiMoO4 good intrinsic activity. Inspired by this, an anion-modified (S - The NiS / NiMoO4 catalyst exhibited excellent catalytic activity and long-term durability under alkaline conditions, thanks to faster electron transfer, more catalytic active sites, and improved reaction kinetics. When the current density was 10 mA cm 2 The overpotential of HER is only 68mV in alkaline medium, and the overpotential of OER is only 128mV in alkaline medium. At the same time, when NiS / NiMoO4 is used as a bifunctional electrode for HER constant current stability test, it can achieve 100mAcm 2 The high current density is basically achieved with a low voltage of 0.275V and can be maintained for 30 hours. When conducting the OER constant current stability test, it can achieve 100mAcm 2The high current density is basically 1.63V and can be maintained for 30 hours. This design and synthesis of high-performance transition metal-based electrocatalysts required for large-scale industrial hydrogen production provides a new approach. Summary of the invention

[0004] The purpose of the present invention is to solve the shortcomings of the prior art and propose a method for preparing a high-stability NiS / NiMoO4 electrocatalytic material and its application. The high-stability NiS / NiMoO4 electrocatalytic material is prepared by hydrothermal and sulfurization processes. The catalyst has excellent HER, OER and stability and has good application prospects in industry.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] A method for preparing a high-stability NiS / NiMoO4 electrocatalytic material comprises the following steps:

[0007] Step 1: Dissolve 0.01M (NH4)6Mo7O in 75mL of distilled water. 24 ·4H2O and Ni(NO3)2·6H2O, and the whole solution system was magnetically stirred for 30 minutes to form a uniform solution; subsequently, the above uniform solution was transferred to a 50mL polytetrafluoroethylene-lined autoclave, and the treated nickel foam was immersed therein; then the autoclave was sealed at 150℃ for 6h, washed with deionized water and ethanol several times until neutral, and vacuum dried to obtain NiMoO4 / NF;

[0008] Step 2: Place sulfur powder upstream of nickel foam, place in a tubular furnace, and after sulfurization in a nitrogen atmosphere, wash the nickel foam and dry in a vacuum oven overnight to obtain NiS / NiMoO4 electrocatalytic material.

[0009] Preferably, in step 1, the size of the nickel foam is (1-2)×(2-3) cm 2 , place the nickel foam in 50-100 ml of 2-4 mol / L HCl solution and ultrasonically treat for 5-15 minutes.

[0010] Preferably, in step 2, the mass of the sulfur powder is 0.5 to 3 g.

[0011] Preferably, in step 2, the vulcanization method is: vulcanization in a tubular furnace under a nitrogen atmosphere, the vulcanization temperature is 300-450° C., the holding time is 1-3 hours, and the heating rate is 0.5-2° C. / min.

[0012] Preferably, in step 1 and step 2, washing is performed with deionized water and ethanol for 3 to 5 times.

[0013] Preferably, in step 1 and step 2, the drying is performed in a vacuum oven at a temperature of 50 to 80° C. for 6 to 12 hours.

[0014] The present invention also provides an application of a high-stability NiS / NiMoO4 electrocatalytic material obtained by the above-mentioned preparation method in hydrogen evolution reaction (HER) and oxygen evolution reaction (OER).

[0015] By adopting the above technical solution: the micromorphology of the prepared NiS / NiMoO4 material is a nanorod array, which can adjust the conductivity and catalytic sites without destroying the overall structure of NiMoO4. Benefiting from faster electron transfer ability, more catalytic active sites and improved reaction kinetics, the NiS / NiMoO4 catalyst exhibits excellent catalytic activity and long-term durability under alkaline conditions.

[0016] Compared with the prior art, the present invention has the following beneficial effects:

[0017] 1. The present invention utilizes a hydrothermal method and a sulfurization process to prepare highly stable NiS / NiMoO4 as a nanorod array, and the prepared NiS / NiMoO4 has excellent full water splitting performance.

[0018] 2. The NiS / NiMoO4 electrocatalytic material prepared by the present invention has good cycle performance and can be used continuously for a long time without causing secondary pollution to the environment during the application process.

[0019] 3. The preparation method of the present invention is easy to operate, has low raw material cost, is environmentally friendly and has the potential for large-scale production, and is conducive to industrial application. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a process flow chart of the preparation of the highly stable NiS / NiMoO4 electrocatalyst prepared in Example 1 of the present invention;

[0021] Figure 2 is the XRD pattern of the highly stable NiS / NiMoO4 electrocatalyst prepared in Example 1 of the present invention;

[0022] Figure 3 The SEM photo of the highly stable NiS / NiMoO4 electrocatalyst prepared in Example 1 of the present invention and the mapping photos of the corresponding elements;

[0023] Figure 4 SAED pattern of the highly stable NiS / NiMoO4 electrocatalyst prepared in Example 1 of the present invention;

[0024] Figure 5 This is the XPS spectrum of the highly stable NiS / NiMoO4 electrocatalyst prepared in Example 1 of the present invention;

[0025] Figure 6 The LSV curve of the OER performance of the highly stable NiS / NiMoO4 electrocatalyst prepared in Example 1 of the present invention in a 1M KOH environment;

[0026] Figure 7 The LSV curve of the HER performance of the highly stable NiS / NiMoO4 electrocatalyst prepared in Example 1 of the present invention in a 1M KOH environment;

[0027] Figure 8 The highly stable NiS / NiMoO4 electrocatalyst prepared in Example 1 of the present invention has a conductivity of 100 mA cm in a 1 M KOH environment. 2 Constant current stability effect diagram after 30 hours. DETAILED DESCRIPTION

[0028] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the accompanying drawings, so that those skilled in the art can better understand the advantages and features of the present invention, thereby making a clearer definition of the protection scope of the present invention. The embodiments described in the present invention are only a part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention.

[0029] Reagents:

[0030] Ethanol, sulfur, nickel nitrate hexahydrate, and ammonium molybdate tetrahydrate were all purchased from Shanghai Myrel Chemical Technology Co., Ltd.

[0031] The water used in the experiment was deionized water.

[0032] Unless otherwise specified, other chemical reagents were of analytical grade and could be used directly without further purification or treatment.

[0033] Embodiment 1:

[0034] A method for preparing a high-stability NiS / NiMoO4 electrocatalytic material comprises the following steps:

[0035] (1) Dissolve 0.01M (NH4)6Mo7O in 75mL of distilled water. 24·4H2O and Ni(NO3)2·6H2O, and the whole solution system was magnetically stirred for 30 minutes to form a uniform solution. Subsequently, the above mixed solution was transferred to a 50mL polytetrafluoroethylene-lined autoclave, and the treated nickel foam was immersed therein. The autoclave was then sealed at 150°C for 6h. It was washed several times with deionized water and ethanol until neutral, and vacuum dried to obtain NiMoO4 / NF.

[0036] (2) Weigh 1.2 g of sulfur powder and place it upstream of the nickel foam, and place it in a tube furnace. Under continuous N2 flow conditions, heat the tube furnace to 300°C and keep it warm for 1 hour at a heating rate of 2°C / min. Finally, wash the nickel foam and dry it in a vacuum oven at 60°C overnight to obtain NiS / NiMoO4.

[0037] Embodiment 2:

[0038] (1) Dissolve 0.01M (NH4)6Mo7O in 75mL of distilled water. 24 ·4H2O and Ni(NO3)2·6H2O, and the whole solution system was magnetically stirred for 30 minutes to form a uniform solution. Subsequently, the above mixed solution was transferred to a 50mL polytetrafluoroethylene-lined autoclave, and the treated nickel foam was immersed therein. The autoclave was then sealed at 150°C for 6h. It was washed several times with deionized water and ethanol until neutral, and vacuum dried to obtain NiMoO4 / NF.

[0039] (2) Weigh 2.0 g of sulfur powder and place it upstream of the nickel foam, and place it in a tube furnace. Under continuous N2 flow conditions, heat the tube furnace to 250°C and keep it warm for 1 hour at a heating rate of 2°C / min. Finally, wash the nickel foam and dry it in a vacuum oven at 60°C overnight to obtain NiS / NiMoO4.

[0040] Embodiment 3:

[0041] (1) Dissolve 0.01M (NH4)6Mo7O in 75mL of distilled water. 24 ·4H2O and Ni(NO3)2·6H2O, and the whole solution system was magnetically stirred for 30 minutes to form a uniform solution. Subsequently, the above mixed solution was transferred to a 50mL polytetrafluoroethylene-lined autoclave, and the treated nickel foam was immersed therein. The autoclave was then sealed at 150°C for 6h. It was washed several times with deionized water and ethanol until neutral, and vacuum dried to obtain NiMoO4 / NF.

[0042] (2) Weigh 1.8 g of sulfur powder and place it upstream of the nickel foam, and place it in a tube furnace. Under continuous N2 flow conditions, heat the tube furnace to 350°C and keep it warm for 1 hour at a heating rate of 2°C / min. Finally, wash the nickel foam and dry it in a vacuum oven at 60°C overnight to obtain NiS / NiMoO4.

[0043] The X-ray diffraction spectrum (XRD) of the NiS / NiMoO4 electrocatalytic material prepared in Example 1 is as follows: Figure 2 shown. Figure 2 It can be seen that the diffraction peaks correspond to the active species of NiS (PDF#12-0041) and NiMoO4 (PDF#45-0142), respectively.

[0044] The SEM image of the NiS / NiMoO4 electrocatalytic material prepared in Example 1 is as follows: Figure 3 As shown. Figure 3 In the figure, the morphology of the final material NiS / NiMoO4 material was characterized, and the image showed the distribution of each element Ni, Mo, O and S in the NiS / NiMoO4 material.

[0045] The SAED image of the NiS / NiMoO4 electrocatalytic material prepared in Example 1 is as follows: Figure 4 As shown. Figure 4 The SAED images in further prove the existence of these phases, where 0.161 nm, 0.312 nm, and 0.205 nm correspond to the (154) plane of NiS (PDF#12-0014), the (112) plane and the (311) plane of NiMoO4 (PDF#45-0142), respectively.

[0046] The XPS image of the NiS / NiMoO4 electrocatalytic material prepared in Example 1 is as follows: Figure 5 As shown. Figure 5 It is not difficult to see in a that Ni, Mo, S and O elements are all present in the NiS / NiMoO4 nanocomposite material prepared by the present invention. Figure 5 In bd, the high-resolution photoelectron spectra of Ni 2p, Mo 3d, S2p, and O 1s are given. The high-resolution spectrum of Ni 2p shows that the strong peaks near 856.3eV and 874.0eV are attributed to Ni 2p, Mo 3d, S2p, and O 1s, respectively. 3 / 2 and Ni 2p 1 / 2 In addition, the peaks at 861.5eV and 880.0eV are respectively attributed to the corresponding satellite peaks. The high-resolution energy spectrum of Mo 3d shows that the strong peaks near 224.2eV and 229.0eV are respectively attributed to Mo3d 3 / 2 ,Mo 3d 5 / 2 According to the high-resolution photoelectron spectrum of S2p, the peak at 168.9eV is attributed to the SO component, while the peaks at 163.5eV and 162eV are attributed to S2p, respectively. 1 / 2 and S2p 3 / 2The O 1s high-resolution spectrum shows a strong peak at 533.8 eV, confirming the presence of -OH functional groups, while the peak at 530.3 eV is related to the defective oxygen atoms in nickel molybdate.

[0047] The LSV curve of the OER performance of the NiS / NiMoO4 electrocatalyst material prepared in Example 1 in a 1M KOH environment is as follows: Figure 6 As shown. The NiS / NiMoO4 nanocomposite electrode only needs 174mV overpotential to obtain 100mAcm -2 The catalytic current is much lower than that of the prepared precursor NiMoO4 and NiS electrodes (520mV and 195mV).

[0048] The LSV curve of the HER performance of the NiS / NiMoO4 electrocatalyst material prepared in Example 1 in a 1M KOH environment is as follows: Figure 7 As shown. The NiS / NiMoO4 electrode exhibits an overpotential of 189mV (100mAcm -2 ), which is much lower than that of the precursor NiMoO4 and NiS electrodes (329mV and 249mV respectively).

[0049] The long-term stability of the NiS / NiMoO4 electrocatalytic material prepared in Example 1 in a 1M KOH environment is as follows Figure 8 At 100mA cm -2 The voltage required for the material under current density is small and can be maintained for 30 hours, which shows that the prepared material still has excellent stability under long-term testing conditions.

[0050] In summary, the present invention utilizes a hydrothermal method and a sulfurization process to prepare highly stable NiS / NiMoO4 as a nanorod array, and the prepared NiS / NiMoO4 has excellent overall water splitting performance.

[0051] The description and practice disclosed in the present invention are easy to think and understand for ordinary technicians in the technical field, and several improvements and modifications can be made without departing from the principles of the present invention. Therefore, modifications or improvements made without departing from the spirit of the present invention should also be regarded as the protection scope of the present invention.

Claims

1. A method for preparing a high-stability NiS / NiMoO4 electrocatalytic material, characterized in that: The steps include: Step 1: Dissolve 0.01M (NH4)6Mo7O in 75mL of distilled water. 24 ·4H2O and Ni(NO3)2·6H2O, and the whole solution system was magnetically stirred for 30 minutes to form a uniform solution; then, the uniform solution was transferred to a 50mL polytetrafluoroethylene-lined autoclave, and the treated nickel foam was immersed therein; Then the autoclave was sealed at 150 °C for 6 h, washed with deionized water and ethanol several times until neutral, and dried in vacuum to obtain NiMoO4 / NF; Step 2: Place sulfur powder upstream of nickel foam, place in a tubular furnace, and after sulfurization in a nitrogen atmosphere, wash the nickel foam and dry in a vacuum oven overnight to obtain NiS / NiMoO4 electrocatalytic material.

2. The method for preparing a high-stability NiS / NiMoO4 electrocatalytic material according to claim 1, characterized in that: In step 1, the size of the nickel foam is (1-2) x (2-3) cm 2 , place the nickel foam in 50-100 ml of 2-4 mol / L HCl solution and ultrasonically treat for 5-15 minutes.

3. The method for preparing a high-stability NiS / NiMoO4 electrocatalytic material according to claim 1, characterized in that: In step 2, the mass of sulfur powder is 0.5 to 3 g.

4. The method for preparing a high-stability NiS / NiMoO4 electrocatalytic material according to claim 1, characterized in that: In step 2, the vulcanization method is: vulcanization in a tubular furnace under a nitrogen atmosphere, the vulcanization temperature is 300-450° C., the holding time is 1-3 hours, and the heating rate is 0.5-2° C. / min.

5. The method for preparing a high-stability NiS / NiMoO4 electrocatalytic material according to claim 1, characterized in that: In step 1 and step 2, washing is performed with deionized water and ethanol for 3 to 5 times.

6. The method for preparing a high-stability NiS / NiMoO4 electrocatalytic material according to claim 1, characterized in that: In step 1 and step 2, the drying is carried out in a vacuum oven at a temperature of 50 to 80° C. for 6 to 12 hours.

7. Use of a high-stability NiS / NiMoO4 electrocatalytic material obtained by the preparation method according to any one of claims 1 to 6 in hydrogen evolution reaction and oxygen evolution reaction.

Citation Information

Patent Citations

  • Transition metal phosphide nanowire as well as preparation method and application thereof

    CN106882774A

  • Molybdate nano composite material as well as preparation method and application thereof

    CN107663637A

  • Self-supporting one-dimensional nanorod array composite material as well as preparation method and application thereof

    CN116516383A